Gene expression analysis of Coffea arabica seeds processed under different post-harvest processing methods - Pallavicini, Alberto; Devasia, Jeena; Paolo Edomi, Martina Modonut,; Lorenzo Del Terra, Luciano Navarini, (Journal of Plantation Crops, 2019)
The mode of coffee processing, either the wet or dry method, determines the characteristic flavour and establishes the differences in quality of the final green coffee produced. The present study focused mainly on identifying the differential gene expression in green coffee seeds of Brazilian arabica coffee (Coffea arabica L.) among samples prepared under three different post-harvest treatments (natural, washed and semi washed method) and grown in two different locations. Expression levels of 16 genes of interest were measured. These genes are involved in various cellular, metabolic and biochemical activities influencing levels of certain compounds, such as lipids, carbohydrates, caffeine and chlorogenic acid, associated with quality characteristics of the beverage. Microarray experiments were designed with cDNA probe sequences. Microarray data was analyzed to identify the differences in gene expression between two altitudes and between two variables: location and post-harvest treatment. Cluster analysis was carried out with samples showing similar patterns, which are characteristic to the group. With this approach, it was possible to identify the important genes in C. arabica seeds that have differential (increased or decreased) expression levels. It was also seen that between the location and treatments, location profoundly impacts the levels of gene expression in samples.